Neural mechanisms of peristalsis in the isolated rabbit distal colon: a neuromechanical loop hypothesis - Dinning, Phil G.; Wiklendt, Lukasz; Omari, Taher; Arkwright, John W.; Spencer, Nick J.; Brookes, Simon J. H.; Costa, Marcello (Frontiers in Neuroscience, 2014)
Propulsive contractions of circular muscle are largely responsible for the movements of content along the digestive tract. Mechanical and electrophysiological recordings of isolated colonic circular muscle have demonstrated that localized distension activates ascending and descending interneuronal pathways, evoking contraction orally and relaxation anally. These polarised enteric reflex pathways can theoretically be sequentially activated by the mechanical stimulation of the advancing contents. Here, we test the hypothesis that initiation and propagation of peristaltic contractions involves a neuromechanical loop; that is an initial gut distension activates local and oral reflex contraction and anal reflex relaxation, the subsequent movement of content then acts as new mechanical stimulus triggering sequentially reflex contractions/relaxations at each point of the gut resulting in a propulsive peristaltic contraction. In fluid filled isolated rabbit distal colon, we combined spatiotemporal mapping of gut diameter and intraluminal pressure with a new analytical method, allowing us to identify when and where active (neurally-driven) contraction or relaxation occurs. Our data indicate that gut dilation is associated with propagating peristaltic contractions, and that the associated level of dilation is greater than that preceding non-propagating contractions (2.7 ± 1.4mm v 1.6 ± 1.2mm; P < 0.0001). These propagating contractions lead to the formation of boluses that are propelled by oral active neurally driven contractions. The propelled boluses also activate neurally driven anal relaxations, in a diameter dependent manner. These data support the hypothesis that neural peristalsis is the consequence of the activation of a functional loop involving mechanical dilation which activates polarized enteric circuits. These produce propulsion of the bolus which activates further anally, polarized enteric circuits by distension, thus closing the neuromechanical loop.